PENGARUH PERAN KEPEMIMPINAN DAN MOTIVASI TERHADAP DISIPLIN KERJA : (STUDI PADA PEGAWAI KPH PERHUTANI MAJALENGKA) - Nita Hernita; Masduki (JURNAL AKUNTANSI DAN SISTEM INFORMASI, 2021)
Study aims to determine how the influence of the role of leadership and motivation on work discipline in the study of KPH Perhutani Majalengka employees. This research is a type of quantitative research using a descriptive and verification approach. The population in this study were all employees of KPH Perhutani Majalengka with a total sample of 65 respondents. The sampling technique used was the Saturated Sampling Technique with a total of 65 respondents and made the sample. The data collection technique in this study was a questionnaire using a Likert scale. Data analysis using classical assumption test, multiple regression analysis, coefficient of determination, model feasibility test and partial hypothesis testing. The results showed that the role of leadership and motivation on work discipline was included in the high category. The results of the hypothesis test partially show that the role of leadership and motivation has a significant effect on work discipline